Maximal physiological responses to deep and shallow water running - Dowzer, C. N.; Reilly, T.; Cable, N. T.; Nevill, A. (Ergonomics, 1999)
The maximal physiological responses to treadmill running (TMR), shallow water running (SWR) and deep water running (DWR) while wearing a buoyancy vest were compared in 15 trained male runners. Measurements included oxygen consumption (VO2 max), respiratory exchange ratio (RER) and heart rate (HR). Treadmill running elicited VO2 max and HRmax, which were higher than the peaks attained in both water tests (p < 0.01). VO2 peak averaged 83.7 and 75.3% of VO2 max for SWR and DWR respectively. Peak HR for SWR and DWR were 94.1 and 87.2% of the HRmax reached in the TMR. RER responses were similar between the three modalities. The observations suggest that the training stimulus provided by water is still adequate for supplementary training. While SWR is potentially an efficient method of maintaining cardiovascular fitness, it needs to be investigated further to establish if it is a viable technique for the injured athlete to employ.